As pesquisas em educação básica realizadas no PPGE/FE/UFG - Silva, Marcia Cristina (2014)
This paper presents the results of an exploratory, bibliographical and documentary research linked to the search Fundamentals of Educational Processes PPGE / FE / UFG, which aimed to enable the scientific training of a teacher whose experience line originates in basic education and reflection on the academic production on this level of education. The proposal was developed with the mapping and analysis of trends expressed in dissertations and theses Program Graduate School of Education, Federal University of Goiás, about basic education. By analyzing the themes and theoretical and methodological frameworks of work aimed - to grasp the comprehensive trends that were being developed on the basic education. Were selected from the cut of the theme, 145 works including dissertations and theses, identified and analyzed using a spreadsheet. This material was organized in synthetic clusters, in order to systematize the topics covered and the privileged methodologies. Therefore, was identified as a significant trend in the work, in addition to methodological and theoretical issues, one privileging the issue of teacher training in discussing the issue of basic education. And yet, within this perspective, one joint involved with the discussions on the issue of reflective teacher and teacher knowledge in reflective practice, focusing on aspects related to the practice and teaching. Thus, it is possible to indicate a relative privilege issues relating to policies that guide the training of teachers in basic education and its neoliberal tendencies.